Early results from the HUMDRUM survey: a small, earth-mass planet orbits TOI-1450A - Brady, Madison; Bean, Jacob L.; Seifahrt, Andreas; Kasper, David; Luque, Rafael; Stefánsson, Guđmundur; Stürmer, Julian; Charbonneau, David; Collins, Karen A.; Doty, John P.; Essack, Zahra; Fukui, Akihiko; et al. (The astronomical journal, 2024)
M-dwarf stars provide us with an ideal opportunity to study nearby small planets. The HUnting for M Dwarf Rocky planets Using MAROON-X (HUMDRUM) survey uses the MAROON-X spectrograph, which is ideally suited to studying these stars, to measure precise masses of a volume-limited (<30 pc) sample of transiting M-dwarf planets. TOI-1450 is a nearby (22.5 pc) binary system containing a M3 dwarf with a roughly 3000 K companion. Its primary star, TOI-1450A, was identified by the Transiting Exoplanet Survey Satellite (TESS) to have a 2.04 days transit signal, and is included in the HUMDRUM sample. In this paper, we present MAROON-X radial velocities (RVs) which confirm the planetary nature of this signal and measure its mass at nearly 10% precision. The 2.04 days planet, TOI-1450A b, has R b = 1.13 ± 0.04 R ⊕ and M b = 1.26 ± 0.13 M ⊕. It is the second-lowest-mass transiting planet with a high-precision RV mass measurement. With this mass and radius, the planet’s mean density is compatible with an Earth-like composition. Given its short orbital period and slightly sub-Earth density, it may be amenable to JWST follow-up to test whether the planet has retained an atmosphere despite extreme heating from the nearby star. We also discover a nontransiting planet in the system with a period of 5.07 days and a . We also find a 2.01 days signal present in the systems’s TESS photometry that likely corresponds to the rotation period of TOI-1450A’s binary companion, TOI-1450B. TOI-1450A, meanwhile, appears to have a rotation period of approximately 40 days, which is in line with our expectations for a mid-M dwarf.
Online veröffentlicht: 10. Juli 2024
Gesehen am 13.02.2025